THE EFFECTIVENESS OF CTL MODEL GUIDED INQUIRI-BASED IN THE TOPIC OF CHEMICALS IN DAILY LIFE TO IMPROVE STUDENTS’ LEARNING OUTCOMES AND ACTIVENESS - Fitriani, N. R.; Widiyatmoko, A.; Khusniati, M. (Jurnal Pendidikan IPA Indonesia, 2016)
Science learning in school can be applied by connecting the material in the learning with real life. However in fact science learning process in SMP Negeri 10 Magelang has not emphasized students’ activity to relate science to real life. Learning science using CTL guided inquiry-based model implement the learning in where teacher provides initial questions related issues or events in everyday life, then students do experiments to prove concepts of science guided by teacher.The purpose of this research is to determine the effectiveness the model in topic of learning of chemicals in life to improve students’ learning outcomes and activity. This research was a quasi-experimental research. The research was conducted in SMP Negeri 10 Magelang with 8th grade students as research subjects. The sample in this study was taken using purposive sampling technique then resulting VIIIA as experiment group and VIIIC as control group. The result shows that experiment group’s learning outcomes increased with N-gain value of 0.62 in the medium criteria. Experiment group’s average of learning outcomes is higher than control group based on the calculation t test with tcount ? ttable (5.42 ? 1.67). Experiment group’s activity also increased every meeting, first meeting was 36.9% in less active criteria, the second meeting increased to be quite active of 60.5%, the third meeting was in the active criteria of 78.2%, and the fourth meeting was 81.4% in very active criteria. It can be concluded that the CTL guided inquiry-based model is effective to improve students’ learning outcomes and activity.